2012
DOI: 10.1590/s0004-282x2012000900018
|View full text |Cite
|
Sign up to set email alerts
|

Cervical and axial dystonia in a patient with syringomyelia

Abstract: Abnormal electromyographic activity is commonly found in patients with syringomyelia, but involuntary movements have only rarely been reported 1 .We have reported the case of a patient with large syringomyelia, who developed cervical and axial dystonia. CASE REPORTA 40-year-old woman presented with progressive sensory loss and weakness of the lower limbs, followed by urinary retention. Concomitantly, she developed repetitive

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Involuntary movements are a rare initial presentation of syringomyelia. Only a few studies reporting involuntary movements are currently available in the literature, and only 1 study reported posttraumatic involuntary movements [7‐9]. Myoclonus, tremor, and dystonia were the most commonly presented symptoms in a previous review [10].…”
Section: Discussionmentioning
confidence: 99%
“…Involuntary movements are a rare initial presentation of syringomyelia. Only a few studies reporting involuntary movements are currently available in the literature, and only 1 study reported posttraumatic involuntary movements [7‐9]. Myoclonus, tremor, and dystonia were the most commonly presented symptoms in a previous review [10].…”
Section: Discussionmentioning
confidence: 99%
“…Although the dog did have concurrent CM and syringomyelia, which has been associated with a variety of involuntary movements, we felt the patient’s phenotype was inconsistent with segmental spinal myoclonus or propriospinal myoclonus. We did consider that the patient’s signs could represent a variant of syringomyelic dystonia, which has not been previously reported in dogs [12, 13]. CM is the most common cause of syringomyelia in dogs, but may be an incidental finding in many at risk breeds [14, 15].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, mostly in the form of case studies, movement disorders due to cervical cord lesions were also reported in syringomyelia (16), traumatic cervical spinal cord damage (12,17), cervical cord tumor (18) in addition to demyelinating diseases. The demyelination plaques on the cervical spinal cord in the three MS cases presented here suggested that the dystonias may likely be due to the damage of the somatosensory pathways of the spinal cord.…”
Section: Discussionmentioning
confidence: 99%